PENGARUH KEPEMILIKAN KELUARGA TERHADAP KEBIJAKAN DIVIDEN DENGAN BOARD OF INDEPENDENCE SEBAGAI VARIABEL MODERASI - Poniman .; Sutrisno T; Abdul Ghofar (Universitas Mercu Buana, 2018)
High concentration of family ownership in East Asia has led to agency conflicts between the majority and minority shareholders potentially affecting the company's dividend policy. This study aims to examine the effect of family ownership on dividend policy. This study also examined the role of board of independence as a moderator in strengthening the influence of family ownership on dividend policy. The result proves that family ownership negatively affects dividend policy but with the existence of board of independence, family ownership has positive effect on dividend policy. This study contributes to the theory of agency type II which discusses conflicts between majority shareholders by family and minority that can be eliminated by good corporate governance mechanisms